The Search for Poetic Justice in César Vallejo’s The Black Heralds - Távara Córdova, Francisco (2019)
This article proposes an analysis of the poems «Our bread», «Imperial Nostalgia», «Autochthonous Tercet», «May», «Villager» and «The Miserable Supper». The objective is to explain which are the reflections on justice that Vallejo expresses in these poems of The Black Heralds. In this way, it seeks to enrich ideas about justice associated with the poet’s life experience.